2013
DOI: 10.1136/postgradmedj-2012-131477
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for chronic arthralgia and rheumatoid-like polyarthritis more than 2 years after infection with chikungunya virus

Abstract: CHIKV is associated with a high prevalence of persistent rheumatic symptoms. Physicians need to be aware of CHIKV as a cause of acute and chronic rheumatic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
69
2
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 23 publications
5
69
2
9
Order By: Relevance
“…Other symptoms of CHIKV infection include a rapid onset of high fever, headache, skin rash, and myalgia. Most of the symptoms normally resolve in weeks but can develop into chronic joint problems and, in rare cases, even mortality (6)(7)(8). There is currently no CHIKV-specific treatment and no licensed vaccine that can prevent CHIKV infection (9).…”
Section: Hikungunya Virus (Chikv) Is An Alphavirus Of the Familymentioning
confidence: 99%
“…Other symptoms of CHIKV infection include a rapid onset of high fever, headache, skin rash, and myalgia. Most of the symptoms normally resolve in weeks but can develop into chronic joint problems and, in rare cases, even mortality (6)(7)(8). There is currently no CHIKV-specific treatment and no licensed vaccine that can prevent CHIKV infection (9).…”
Section: Hikungunya Virus (Chikv) Is An Alphavirus Of the Familymentioning
confidence: 99%
“…Clinical manifestations of CHIKV infection include high fever, headache, rash, myalgia, and debilitating arthralgia (7). The infection typically resolves within weeks but can result in chronic joint problems (8,9) or, rarely, mortality (10).…”
mentioning
confidence: 99%
“…In addition to rheumatic disease, CHIKV infection is also associated with fever, headache, rigors, photophobia, myalgia, and a petechial or maculopapular rash (38,39). The acute phase of CHIKV infection typically lasts from days to several weeks; however, multiple studies have reported chronic fatigue and chronic joint pain for a significant time postinfection, with one study demonstrating persistent joint pain in roughly 79% of patients at 27.5 months postinfection, with 5% of those infected with CHIKV meeting a modified version of the American College of Rheumatology criteria for rheumatoid arthritis (14,37,(40)(41)(42)(43)(44)(45). In both human cases and mouse models, CHIKV-induced immunopathology is implicated as the primary mediator of damage and persistent pain (46)(47)(48)(49)(50).…”
mentioning
confidence: 99%